Products of Composition and Differentiation Operators from 𝒬K(p,q) Spaces to Bloch-Type Spaces - Weifeng Yang (Abstract and Applied Analysis)
We study the boundedness and compactness of the products of composition and differentiation operators from 𝒬K(p,q) spaces to Bloch-type spaces and little Bloch-type spaces.